KOLABORASI ORANG TUA DAN GURU DALAM IMPLEMENTASI PROGRAM PENDIDIKAN INDIVIDUAL (PPI) PADA ANAK TUNAGRAHITA DI SEKOLAH DASAR INKLUSI - Eti Nurhayati; Deri Hendriawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to describe the impact of collaboration between parents and teachers in implementing the Individualized Education Program (IEP) for an 11-year-old 5th-grade student with intellectual disabilities in an inclusive elementary school. Previously, the lack of synergy between the school and home caused significant obstacles to the student's academic and adaptive development. The research method used is a qualitative case study with data collection techniques through participant observation, in-depth interviews, and documentation. The results showed that before the collaboration, the student experienced developmental stagnation. After the participatory development of the IEP, accompanied by routine weekly meetings between teachers and parents, the student showed significant progress in functional reading skills and self-independence. Consistency of treatment at school and home became a key factor for success. This study concludes that structured collaboration through the IEP is crucial in optimizing the potential of children with intellectual disabilities.